THE INFLUENCE OF WORDS OF MOUTH AND BRAND IMAGE ON MCDONALDS PRODUCT PURCHASE DECISIONS IN PALEMBANG CITY (CASE STUDY OF WORLD BRANDS THAT SUPPORT ISRAEL) - Zubaidah Warni; Alditya Aris Rinandy (Jurnal Manajemen, 2024)
The war that occurred between Israel and Palestine at the end of 2023 has changed the world'sperception of brands. Especially if the brand supports Israel. The majority of countries carry outboycotts, but in Indonesia several brands that outside the country support Israel actually provideassistance to Palestine. Mcdonalds Indonesia is one of the biggest brands that has actually providedassistance to Palestine since the end of 2023 until now. McDonalds Indonesia itself received anaward from Baznas in 2024 for participating in providing assistance to Palestine. It is hoped that theinfluence of Word of Mouth on this matter will be able to maintain the number of consumers fromboycotting their products in Indonesia, especially since McDonalds has its own Brand Image. It ishoped that this will still be able to maintain the brand image which will ultimately make consumerscontinue to decide to consume McDonalds